The population control bill, 2021: exploring newer perspectives - Nagabhushana, Prerana; Sarkar, Avir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
As we observe the World Population Day on 11th July, the current population stands at roughly 7.9 billion in 2021, with India bagging the second place at 1.39 billion. The net growth rate stands at 1.1% or 83 million per year and the projected world population by 2050 is estimated to be 9.7 billion. These figures are alarming to us-the millennials, who grew up writing ominous essays on ‘population explosion’ at school. Governments across the world, historically Romania to more recently China, have adopted population policies to control the rate of population growth to cater to their advantage-either economically or politically. Some of them directly against reproductive rights- to decide freely and responsibly the number, spacing and timing of their children and to be able to do so without discrimination, coercion and violence.